Role of Chloramphenicol Acetyltransferase (CAT) Enzyme for Early Detection of Chloramphenicol Resistant Salmonella typhi (Indonesian Society for microbiology, 2014)
Microbial resistance to antibiotic is a major problem in the treatment of infectious diseases. The purpose ofthis study was to identification the role of CAT enzyme for early detection of chloramphenicol resistant. Observation was performed on isolated from Dr. Sutomo Hospital, Surabaya Health Laboratory, and Microbiology Laboratory-Airlangga University, Surabaya in 2009 and had been subcultured.The sub-culture was then tested for its susceptibility to chloramphenicol by using anti-chloramphenicol acetyl transferase (CAT) antibody from Sigma (catalog number C.9336). Susceptibility test using dilution and diffusion methods proved that resistant could change to sensitive and vice versa. It seems that the CAT enzyme can bind anti-CAT so reversing the resistant into sensitive and conversely, sensitive into resistant one.